Structural basis of the γ-lactone-ring formation in ascorbic acid biosynthesis by the senescence marker protein-30/gluconolactonase. - Shingo Aizawa (Public Library of Science (PLoS), 2013)
The senescence marker protein-30 (SMP30), which is also called regucalcin, exhibits gluconolactonase (GNL) activity. Biochemical and biological analyses revealed that SMP30/GNL catalyzes formation of the γ-lactone-ring of L-gulonate in the ascorbic acid biosynthesis pathway. The molecular basis of the γ-lactone formation, however, remains elusive due to the lack of structural information on SMP30/GNL in complex with its substrate. Here, we report the crystal structures of mouse SMP30/GNL and its complex with xylitol, a substrate analogue, and those with 1,5-anhydro-D-glucitol and D-glucose, product analogues. Comparison of the crystal structure of mouse SMP30/GNL with other related enzymes has revealed unique characteristics of mouse SMP30/GNL. First, the substrate-binding pocket of mouse SMP30/GNL is designed to specifically recognize monosaccharide molecules. The divalent metal ion in the active site and polar residues lining the substrate-binding cavity interact with hydroxyl groups of substrate/product analogues. Second, in mouse SMP30/GNL, a lid loop covering the substrate-binding cavity seems to hamper the binding of L-gulonate in an extended (or all-trans) conformation; L-gulonate seems to bind to the active site in a folded conformation. In contrast, the substrate-binding cavities of the other related enzymes are open to the solvent and do not have a cover. This structural feature of mouse SMP30/GNL seems to facilitate the γ-lactone-ring formation.